Providing of High Longevity of Operating Parts of Small-Scale Machinery in Agriculture; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Chernysh A. P.; Korchuganova M. A. Marina Anatolievna; Сырбаков А. П. Андрей Павлович; Burunov A. I. (Designing and Modelling of Machines and Mechanisms, 2015)
Title screen